The impact of inflammatory and metabolic markers on depression, anxiety, and cognition after COVID-19: a narrative review - Elton Jorge Bessa Diniz; Fulvio Alexandre Scorza; Fabrício Maués Santos Rodrigues; Claudia Berlim de Mello; Tatiana Carvalho de Souza Bonetti; Karina Ramalho Bortoluci; Jair de Jesus Mari (Trends in Psychiatry and Psychotherapy)
Abstract Objectives: There has been growing concern about the long-term effects of coronavirus disease 2019 (COVID-19) on mental health. The biological factors common to psychiatric conditions and COVID-19 are not yet fully understood. Methods: We narratively reviewed prospective longitudinal studies that measured metabolic or inflammatory markers and assessed psychiatric sequelae and cognitive impairment in individuals with COVID-19 at least 3 months after infection. A literature search identified three relevant cohort studies. Results: Overall, depressive symptomatology and cognitive deficits persisted for up to 1 year after COVID-19; depression and cognitive changes were predicted by acute inflammatory markers, and changes in these markers correlated with changes in depressive symptomatology; female sex, obesity, and the presence of inflammatory markers were associated with more severe clusters of physical and mental health status in patients’ self-perceived recovery; and plasma metabolic profiles of patients continued to differ from those of healthy controls 3 months after hospital discharge, which were associated with widespread alterations in neuroimaging, reflecting issues with white matter integrity. Conclusion: In individuals affected by COVID-19, prolonged exposure to stress and alterations in metabolic and inflammatory markers play a central role in psychiatric sequelae and cognitive deficits in the long term.